2011
DOI: 10.1111/j.1439-0531.2010.01594.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Differentiation of Mesenchymal Stem Cells From Bovine Umbilical Cord Blood

Abstract: Currently, mesenchymal stem cells (MSCs) are used in veterinary clinical applications. Bone marrow and adipose tissue are the most common sources of stem cells derived from adult animals. However, cord blood which is collected non-invasively is an alternative source of stem cells other than bone marrow and adipose tissue. Moreover, high availability and lower immunogenicity of umbilical cord blood (UCB) haematopoietic stem cells compared to other sources of stem cell therapy such as bone marrow have made them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 23 publications
7
37
0
Order By: Relevance
“…Previous reports have described the isolation of MSC from several species and tissues; however, to our knowledge, isolation of ASC from bovines and buffalos has not yet been done (Bosnakovski et al, 2005;Rodriguez et al, 2005;Yamamoto et al, 2007;Neupane et al, 2008;de Mattos Carvalho et al, 2009;Bourzac et al, 2010;Raoufi et al, 2011). The ASC we isolated from bovines and buffalos in this study display similar characteristics (i.e., cell morphology, doubling time, and multilineage differentiation potential) to those previously reported for MSC isolated from other species and tissues.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previous reports have described the isolation of MSC from several species and tissues; however, to our knowledge, isolation of ASC from bovines and buffalos has not yet been done (Bosnakovski et al, 2005;Rodriguez et al, 2005;Yamamoto et al, 2007;Neupane et al, 2008;de Mattos Carvalho et al, 2009;Bourzac et al, 2010;Raoufi et al, 2011). The ASC we isolated from bovines and buffalos in this study display similar characteristics (i.e., cell morphology, doubling time, and multilineage differentiation potential) to those previously reported for MSC isolated from other species and tissues.…”
Section: Discussionsupporting
confidence: 69%
“…Cells were plated at a density of 3 x 10 4 or 4 x 10 4 cells per 35-mm plate and replated every two and three days for bovines and buffalos, respectively. Cell doubling time was estimated in triplicate as described by Raoufi et al (2011).…”
Section: Isolation and Culture Of Ascmentioning
confidence: 99%
“…As such, gestational tissues including umbilical cord blood (Kern et al 2006, Koch et al 2007, Guest 2008, Reed & Johnson 2008, Bartholomew et al 2009, Schuh et al 2009, Seo et al 2009, Raoufi et al 2011, umbilical cord tissues (Mitchell et al 2003, Carlin et al 2006, Hoynowski et al 2007, Cremonesi et al 2008, Passeri et al 2009, Lovati et al 2011, Iacono et al 2012a, amniotic tissues (Filioli Uranio et al 2011, Iacono et al 2012a, 2012b, Lange-Consiglio et al 2012, and amniotic fluid (AF) (Chen et al 2011, Dev et al 2011, Lovati et al 2011, Iacono et al 2012a) have been recently suggested, also in veterinary medicine, as appealing candidates for the derivation of MSCs to use in cell biotechnology. The human lesson teaches that presumptive adult stem cells derived from gestational tissues retain highest proliferation capacity, longest telomere length, broadest differentiation, and extensive proliferative potential when compared with cells obtained from adult tissues (Kogler et al 2004, Kern et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…So far, they have been derived from umbilical cord blood (Raoufi et al 2011) and bone marrow (Bosnakovski et al 2005(Bosnakovski et al , 2006 and attempts to isolate cells from the amniotic membrane or from the AF have not been reported in the literature yet.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have described the isolation of MSC from several species and tissues; however, to our knowledge, isolation of ASC from bovines and buffalos has not yet been done (Bosnakovski et al, 2005;Rodriguez et al, 2005;Bourzac et al, 2010;Raoufi et al, 2011). The ASC we isolated from bovines and buffalos in this study display similar characteristics (i.e., cell Bovine and buffalo mesenchymal cells morphology, doubling time, and multilineage differentiation potential) to those previously reported for MSC isolated from other species and tissues.…”
Section: Discussionsupporting
confidence: 65%